Muslim, trader, nomad, spy : China's Cold War and the people of the Tibetan borderlands - Khan, Sulmaan Wasif (New Cold War history., 2015)
"What Chinese policymakers confronted in Tibet, Khan argues, was not a 'third world' but a 'fourth world' problem: Beijing was dealing with peoples whose ways were defined by statelessness. As it sought to tighten control over the restive borderlands, Mao's China moved from empire-lite to a harder, heavier imperial structure. That change triggered long-lasting shifts in Chinese foreign policy. Moving from capital cities to far-flung mountain villages, from top diplomats to nomads crossing disputed boundaries in search of pasture, this book shows Cold War China as it has never been seen before and reveals the deep influence of the Tibetan crisis on the political fabric of present-day China"--Provided by publisher